Islamic Law and Community Economic Empowerment - Samsuddin; Ummul Wafiyah; Ekawati Hamzah (International Journal of Integrative Sciences, 2023)
This research is about "Islamic Law and Community Economic Empowerment", the Islamic economic system emphasizes the creation of equitable income distribution, not only to fulfill individual interests but also public interests. This study used a descriptive method, by elaborating information in relevant literature. The data collection technique in this study is a documentary technique, specifically, the information is extracted through documents from various library materials, after that it was analyzed by using content analysis, namely, examining the object of discussion through analysis of books, essays, magazines, articles and all forms of communication that can be analyzed. The results of this study indicate that community economic empowerment in Islam, the emphasis is not only on increasing income and investment, but also on eliminating the causes of poverty. Community economic empowerment requires strategic steps such as socializing and educating the society about the importance of building a sharia economy, strengthening the economic institutions of the people, strengthening the role of Amil Zakah and economic cooperation and strengthening the role of government